Wind regime and sand transport in the mid-course of ten tributaries of the Yellow River, Inner Mongolia of China - Zhao, Hongsheng; Feng, Shuang; Dang, Xiaohong; Meng, Zhongju; Chen, Zhengxin; Gao, Yong (Frontiers in Environmental Science, 2023)
Better understanding the wind regimes and dune activity criteria are pre-requisites for the successful planning of any sand dune fixation project and hence have a high priority.To fully understand wind energy conditions and the intensity of aeolian activity, we investigated the wind conditions, sand-transporting potential, and sand-transporting capacity of the basins of mid-course ten tributaries of the Yellow River through field observations and indoor analyses. The analysis of wind energy, which is based on sand transport potential, demonstrates that there is substantial spatial variation within the study area. The western part, which is located near the Kubuqi Desert, qualifies as a high wind energy zone. In contrast, the central part belongs to the medium wind energy zone, whereas the eastern part is categorized as a low wind energy zone. Even though there are notable differences in the sand transport potential characteristics across different time scales, the direction of the synthesized sand transport potential tends to be consistent, predominantly leaning towards the southeast. This orientation provides the requisite energy for the sand material to be transported into the river.The prevailing sand-producing wind direction at various timescales in the research area was dominated by westward (W, WNW, NW) and northward (NNW, N) winds, with distinct seasonality. This seasonal variability was especially prominent in spring, which saw the highest frequency of aeolian activity and the largest volume of sand transport. Autumn and winter exhibited similar patterns, and, in the summer, it was the lowest The relationship between sand-transporting potential and sand-transporting capacity, which is a crucial aspect of aeolian geomorphology, could be adequately depicted using a fitting function based on the temporal patterns of wind speed. During periods of high wind, the sand-transporting potential and sand-transporting capacity of the basins of the ten tributaries followed a power function relationship. Conversely, during periods of low wind, they followed an exponential function relationship. These results imply that spring should be deemed as the crucial period for wind-sand prevention and control. Additionally, emphasis should be placed on the western part, which is situated close to the sand source area, as the primary prevention and control zone.